How leaders' experiences and rebellion shape military recruitment during civil war. (September 2021) - Chaudhry, Suparna; Karim, Sabrina; Scroggs, Matt K
The use of forced recruitment strategies during war can adversely affect military effectiveness and human rights. Given these costs, under what conditions do state leaders adopt coercive recruitment during civil wars? We find that between 1980 and 2009, states changed their recruitment practices 140 times during civil wars – half of which were towards coercive recruitment. Since structuralist explanations focus on factors that remain more or less constant over time, they cannot explain the frequency of these changes. Instead, we focus on individual-level factors and argue that leaders' dispositions as risk-takers determine their beliefs about using force to solve collective action dilemmas during civil wars. Further, conflict context matters for leaders' recruitment decisions – when rebel groups engage in coercive recruitment, leaders may also feel more justified in using such strategies. Using the LEAD Dataset and data on recruitment, we find that risk-tolerant leaders, including those who have had careers in the security sector, as well as those who have prior experience as a rebel or revolutionary leader, are more likely to use force to increase recruitment. While we theorize that this effect may be mitigated by combat experience, the evidence is mixed. Lastly, we find that rebels' use of forced recruitment makes state leaders less likely to use voluntary recruitment.